ANALISIS HAMBATAN PESERTA DIDIK KELAS V DALAM PEMBELAJARAN SENAM LANTAI GULING DEPAN DI SD 104241 KELURAHAN KAMPUNG SYAHMAD. - Fitria adi Ningsih; Winara; Irsan; Edizal Hatmi; Khairul Usman (STKIP Subang, 2026)
This study aims to determine the obstacles experienced by fifth-grade students in performing forward roll floor gymnastics at SD 104241, Kampung Syahmad Village, with a total of 49 students as subjects. This study uses a qualitative descriptive method. Data collection techniques were carried out through questionnaires, interviews, and observations, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. Data validity was obtained through source and method triangulation techniques to ensure the validity of the research findings. Based on field findings, learning obstacles include physical, psychological, material, teacher, facilities and infrastructure, as well as environmental and time aspects. The results of the analysis show that the most dominant obstacles are in the facilities and infrastructure aspect, especially limited facilities such as inadequate mattresses, thus hampering the implementation of optimal and safe learning for students. In addition, environmental and time aspects are also classified as having quite high obstacles, such as the condition of the learning place that is less supportive and limited allocation of learning time. Physical, psychological, material, and teacher aspects have relatively lower levels of obstacles. Thus, it can be concluded that the main obstacles in learning forward roll floor gymnastics are more influenced by external factors. Therefore, efforts are needed from schools and teachers to improve learning facilities and create more effective, innovative, and enjoyable learning conditions so that learning objectives can be achieved optimally.